Isolation and Characterization of Thymineless Mutants from Ultraviolet-Sensitive Bacillus subtilis Strains - Felkner, Ira C. (1970)
Thymineless mutants of Bacillus subtilis 168 ind, hcr-9 were isolated by using trimethoprim. These and other Thy(−) strains differed drastically from Thy(+) ones in their patterns of [(3)H]thymidine uptake and growth in trimethoprim-containing medium. Transformation was negligible between most mutants derived from the ultraviolet-sensitive strain 168 ind, hcr-9 but significant between 168 ind, thy and these mutants. The latter and these new mutants all grow in the presence of trimethoprim plus thymidine or thymine and fail to grow if thymine or thymidine is omitted.